Bypass Inductor Type LCL Filter Parameter Optimization for Three-Level Grid-Connected Converter - Li , Ning; Zhang , Shiqian; Xiao , Zihan; An, Zhuoer; Zhang, Yan; Jiang, Lin (Frontiers in Energy Research, 2022)
In the application of the three-level grid-connected system, passive damping is the most common method to keep the LCL filter working stably. However, in the case of high power density, the low switching frequency of the grid-connected converter results in the complexity of filter parameter design, and the increase of passive components leads to lower equipment utilization efficiency. To solve the above problems, based on the optimization of resonant frequency and the system loss, this paper proposes a set of LCL filter parameter design process of three-level NPC ( Neutral Point Clamped) converter, which can switch components freely and is easy to achieve. Taken into account the influence of current ripple and the reactive power limit, this paper explores the theoretical evidence and application value of the proposed design. The design adopts the improved passive damping method to select the appropriate inductance ratio and impedance ratio to achieve the minimum resonance frequency of the whole system and reduce the extra loss of the system. The simulation and experiments show that, compared with the conventional method, the improved design method reduces the current THD of the grid side by 1.5% and the damping resistance loss by 0.17%.